Methodology for the feasibility assessment of an eco-transfer system. (June 2022) - Pérez-Guzmán, Sofía; Wang, Cara; Conway, Alison; Arrieta-Prieto, Mario E.; Ding, Yue; Zuman, Gregg S.; Escand, Pierre; Chen, Quanquan
Abstract: With outdated parking space, land use and curbside management practices rampant in dense urban areas, researchers and practitioners over the past decade have proposed several innovative schemes to encourage a shift in urban delivery and logistics behavior. The success of such schemes, however, has proven more challenging than anticipated, as it depends on accounting for a myriad of factors. This research proposes a methodology to assess the feasibility of implementing a successful Eco-Transfer System (ETS) initiative. An ETS consists of transfer locations for transferring goods between large vehicles and sustainable city-scaled modes, such as cargo cycles and hand carts, for urban delivery. The methodology considers a supply–demand quantification, together with a study on market conditions and infrastructure requirements, as well as a legal framework investigation. The methodology was used for the case of New York City (NYC). The results indicate that an Eco-Transfer System in NYC could be implemented successfully under certain conditions. The city has features, such as its geography and demand, that are appropriate for the system to succeed. The market conditions also foreshadow its success. In addition, the authors identify opportunities concerning stakeholder engagement.